Language unlimited the science behind our most creative power - Adger, David (Oxford Oxford University Press, 2019)
All humans, but no other species, have the capacity to create and understand language. It provides structure to our thoughts, allowing us to plan, communicate, and create new ideas, without limit. Yet we have only finite experiences, and our languages have finite stores of words. Where does our linguistic creativity come from? How does the endless scope of language emerge from our limited selves?0Drawing on research from neuroscience, psychology, and linguistics, David Adger takes the reader on a journey to the hidden structure behind all we say (or sign) and understand. Along the way you'll meet children who created language out of almost nothing, and find out how new languages emerge using structures found in languages spoken continents away. David Adger will show you how the more than 7000 languages in the world appear to obey the same deep scientific laws, how to invent a language0that breaks these, and how our brains go crazy when we try to learn languages that just aren't possible. You'll discover why rats are better than we are at picking up certain language patterns, why apes are far worse at others, and how artificial intelligences, such as those behind Alexa and Siri, understand language in a very un-human way. 0Language Unlimited explores the many mysteries about our capacity for language and reveals the source of its endless creativity.
Includes bibliographical references and index.
Keywords: Creativity (Linguistics); Language and languages -- Philosophy